THE APPLICATION OF WATERMARKING REGION OF INTEREST (ROI) DIGITAL IMAGE METHOD DISCRETE WAVELET TRANSFORM (DWT) MORPHOLOGY AND MATHEMATICAL - Made Dyah Aryani (Universitas Pendidikan Ganesha, 2013)
This research was aimed to design and to implement the application region of interest (ROI) digital images with discrete wavelet method transform (DWT) and mathematical morphology. Input of this application is a color image format *. Bmp, and the output of this application is an image too watermak.This software only handles the process of embedding and extraction. Theprocess of embedding a process to insert watermark into a digital image that has been through the discrete wavelet transform, while the watermark extraction is a separation process of the image carrier. In this software also added features for selecting parts of images that will be used as a digital watermark is to apply the Region of Interest (ROI) of digital images, the next part of this selection will be disguised by Mathematical Morphology.The result of this study is an application of watermarking region of interest(ROI) digital images with discrete wavelet method transform (DWT) and mathematical morphology. This software is created with Borland Delphi 7.0. The software is also implemented and has been tested on Windows based operating systems.